ESP Materials Evaluation of the Psychology Students at Bahauddin Zakariya Universty and its Affiliated Colleges in Multan - Masood, Faiza; Rubab, Iram (Pakistan Languages and Humanities Review, 2022)
This article is an attempt to explain the process that took place to evaluate English material for the Psychology students at BZU and its affiliated colleges in Multan. This research aimed to determine the suitability of the English material for the students of this particular discipline in the academic context. To achieve this goal, one questionnaire comprised of the following 10 items (physical qualities of the text, content and subject matter, specific vocabulary, reading skills, writing skills, listening skills, speaking skills, illustrative material, supplementary material, and the availability of the material) was formulated. The participants included 40 Masters Students and 60 BS students of the Psychology Department from BZU and its affiliated colleges in Multan. The collected data were quantitatively analyzed. The findings presented a clear picture of the less suitability and effectiveness of the existing ESP material for Psychology students in the academic context. Thus, through this study, the effectiveness of the existing ESP material in the discipline of Psychology was investigated and suitable related material according to the academic needs of the Psychology students is suggested.